2021
DOI: 10.1177/00472816211044498
|View full text |Cite
|
Sign up to set email alerts
|

User Experience in Health & Medicine: Building Methods for Patient Experience Design in Multidisciplinary Collaborations

Abstract: Health and medical contexts have emerged as an important area of inquiry for researchers at the intersection of user experience and technical communication. In addressing this intersection, this article advocates and extends patient experience design or PXD ( Melonçon, 2017 ) as an important framework for user experience research within health and medicine. Specifically, this article presents several PXD insights from a task-based usability study that examined an online intervention program for people with voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Complications arose in terms of site location—the campus was unfamiliar to most participants and campus sporting events caused disruptions to driving routes and parking availability—therefore, for the last 2 tests, we moved to a research suite closer to the voice clinic familiar to participants, although the suite did not include high-quality data recording or a one-way mirror. We have discussed these challenges in greater detail elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complications arose in terms of site location—the campus was unfamiliar to most participants and campus sporting events caused disruptions to driving routes and parking availability—therefore, for the last 2 tests, we moved to a research suite closer to the voice clinic familiar to participants, although the suite did not include high-quality data recording or a one-way mirror. We have discussed these challenges in greater detail elsewhere [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…A moderator facilitated each usability test and asked participants to complete each task using a think-aloud protocol (in which participants share their thoughts as they work through the task [ 25 ]). An additional research question, which focused on understanding patient experiences with the intervention, was added during usability testing [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are various systems in nursing homes affecting an individuals' quality of life, food service quality proves to be of significance in longterm care facilities (Jeong & Seo, 2014). Accordingly, the evaluation of patient experiences (PX) within healthcare can improve the overall engagement, respectfulness, and responsiveness of food service systems through demonstrating relationships among human activities, perspectives, and satisfaction with information or technology (Kessler et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As part of the same special issue collection, Lanius et al (2021) demonstrated some aspects of this foregrounding exercise by showcasing current trends in UX methods and their implications for TPC practice. Two other entries in the special issue applied UX methods in healthcare and patient experience contexts (Kessler et al, 2021; St.Amant, 2021). Both of these entries showed the applicability of UX in medical settings, a research space familiar to TPC scholars.…”
Section: Introductionmentioning
confidence: 99%